PEMBUATAN DAN KARAKTERISASI PLAFON YANG DIBUAT DARI SERBUK BATANG KELAPA SAWIT DAN SERBUK AMPAS TEBU DENGAN MENGGUNAKAN PEREKAT EPOKSI - Meilan Agustina Sitorus (Saintia Fisika, 2013)
ABSTRACT   Studies have been for the preparation and characterization ceiling that made from oil palm stem powder and sugar cane waste by epoxy as adhesive .The variations of oil palm stem powder and sugar cane waste mixture as an independent variable with composition variations (4:0) gr, (3:1) gr, (2:2) gr, (1:3) gr, (0:4) gr. Then added by 8 ml of epoxy adhesive as fixed variables. The results showed that a good mix is a mixture (2:2) gr which has physical properties (density 1,14 gr/cm3, water absorption 11,39%) and the testing of mechanical properties (5 kJ/m2 impact test, flexural test 18,81 MPa, tensile strength test of 10,38 MPa), these results meet the standard of ISO 03 – 2105, 2006. Test results of DTA obtained the melting point 435 oC and critical point is 345 oC, with the results that the composition of (2:2) gr can be used as a ceiling.   Key words : Ceiling, Oil palm stem powder, sugar cane waste, epoxy resin